Defect structure of Czochralski silicon co-implanted with helium and hydrogen and treated at high temperature - pressure - Wierzchowski, W.; Misiuk, A.; Wieteska, K.; Bak-Misiuk, J.; Jung, W.; Shalimov, A.; Graeff, W.; Prujszczyk, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Effect of stress created by Ar hydrostatic pressure (HP) up to 1.1 GPa during annealing at the high temperature (HT) 1070 K (HT-HP treatment) on microstructure of Czochralski grown silicon co-implanted with helium and hydrogen Si:(He,H) using the same doses of He+ and H₂+ (DH,He= 5·10¹⁶ cm⁻², at energy 50 and 150 keV, respectively) was investigated by means of X-ray (synchrotron) diffraction, transmission electron microscopy, and electrical measurements. The nanostructured sponge-like buried layers are formed in Si:(He,H) by annealing / high pressure treatment. Decreased interference, diffuse scattering and individual contrast are observed in the synchrotron topograms for HT-HP treated Si:(He,H). The treatment at 723 K and HP results in an additional donor formation as a sequence of the implantation-disturbed layer. The HP-mediated (retarded) out-diffusion of hydrogen and helium is in part responsible for the effects observed.